(untitled) (Entrepreneurship Journal for Finance and Business, 2021)
The study aims to determine the level of techniques used in the State Company for Electrical Industries to optimize the supply chain that seeks to meet the needs and requirements of customers. In order for the company to survive and grow, especially in light of the increasing competition, it must develop or update its production system in line with the business environment, This study came to address the problem faced by the State Company for Electrical Industries, . The study relied on the descriptive and analytical approach in surveying the opinions of the study sample members in the General Company for Electrical Industries in collecting data and information needed for modern technologies and streamlining the supply chain in the practical aspect. Various specializations (administrative, engineering and technical) by (84%), the results were analyzed with the adoption of the statistical program SSPS V.25). And that the company’s management gives attention to streamlining the supply chain and is interested in maintaining the level of performance of its production operations by following the necessary procedures and instructions in order to reduce the negative effects on production processes to the maximum extent possible